Composition of broilers meat - De Oliveira, J. [UNESP]; Avanço, S. V. [UNESP]; Garcia-Neto, M. [UNESP]; Ponsano, E. H.G. [UNESP] (Elsevier, 2016)
Brazil stands out in the ranking of broiler chicken production, holding the positions of the world's largest exporter and the third largest producer, scores that demand continuous attention to market requirements with regard to product quality, including the search for alternative sources of feed ingredients. This research's goal was to examine the effects of using Rubrivivax gelatinosus biomass in the feed of broilers on proximate composition, cholesterol content, and fatty acid profile of the meat cuts. Two hundred Cobb 500 male chicks were randomly assigned to one of the 4 dietary treatments containing zero, one, 2 or 3 g of dried R. gelatinosus biomass per kg of the finisher ration. At the end of the experiment, 20 birds from each treatment were slaughtered and their carcasses were cut into breast and thigh for the analyses of proximate composition, cholesterol, and fatty acids, all performed by standard methodologies. Data were analyzed by ANOVA and t test for the multiple comparisons of means using 5% of significance. Proximate composition and cholesterol concentration in both breast and thigh meats did not differ among treatments (P > 0.05). The biomass at 3 g/kg in the diet increased EPA in breast but decreased it in thigh. Nevertheless, no concentration of the biomass altered the ratio n-6/n-3 in either cut. Thus, the use of R. gelatinosus biomass at 3 g/kg in broilers' rations was shown to be harmless or even beneficial to broiler meat composition.
Keywords: cholesterol; fatty acids; food composition; Rubrivivax gelatinosus